APPLICATION OF THE BRAHMAVIHARA DHAMMA PRINCIPLE TO PROMOTE THE ADMINISTRATION OF LOCAL POLITICIANS IN BAN KUM SUBDISTRICT ADMINISTRATIVE ORGANIZATION, MUEANG DISTRICT, PHETCHABURI PROVINCE - สาตร์สาคร ทศพล; Bhalakula, Anucha; Akhomtiro, Phra Samu Akhom (Journal of MCU Phetchaburi Review, 2025)
This mixed-method research aimed to 1) study the level of local politicians’ administration in Ban Kum Subdistrict Administrative Organization; 2) compare the administration of local politicians in Ban Kum Subdistrict Administrative Organization by personal factors; and 3) propose the application of the Brahmavihara Dharma principle to promote the administration of local politicians in Ban Kum Subdistrict Administrative Organization. The sample consisted of 372 residents in Ban Kum Subdistrict Administrative Organization aged 18 years and over and 9 key informants. Data were analyzed by percentage, mean, standard deviation, F-test using one-way ANOVA, and descriptive content analysis. The results of the study revealed that 1) the overall level of local politicians’ administration in Ban Kum Subdistrict Administrative Organization is at a high level. 2) The results of the comparison of local politicians’ administration in Ban Kum Subdistrict Administrative Organization by personal factors revealed that people of different ages and occupations have different opinions on the administration of local politicians in Ban Kum Subdistrict Administrative Organization. Overall, the difference was statistically significant at the 0.05 level. 3) The application of the principles of Brahmavihara Dhamma to promote the administration of local politicians in the Ban Kum Subdistrict Administrative Organization is to incorporate loving-kindness, compassion, mudita, and equanimity in their operations. Kindness promotes development and cares for the people; compassion emphasizes reducing inequality and helping those in need; mudita congratulates others on their success; and equanimity creates fairness, integrity, and credibility in administration. All of this helps create local politics that is transparent, sustainable, and ethical.